Mencari Peluang Agribisnis Melalui Usaha Kentang G4 Sertifikat - Anton Gunarto (Jurnal Matematika Sains dan Teknologi, 2004)
The article discusses the application of potato cultivation technology, process of G4 potato tuber seed production, and economic analysis for G4 potato tuber seed agribusiness. The method used in the research is cultivating G4 potato tuber seed on two different seasons, wet and dry season. The economic analysis shows that the G4 potato tuber seed agribusiness is beneficial. Research shows that production of G4 potato tuber seed on wet season is 25,684 ton per 1,2 Ha with net profit Rp. 25.798.800 and B/C ratio 1.52. On dry season, the production is 19,294 ton/Ha with net profit Rp. 10.247.950 and B/C ratio 1.21. The G 4 potato tuber seed agribusiness gives more benefit than potato consumption tuber agribusiness, although they provide adequate profit.